KAJIAN EFEK INTERAKSI OBAT GOLONGAN STATIN DENGAN CALCIUM CHANNEL BLOCKER (CCB) TERHADAP RHABDOMIOLISIS - Marathus Sholikhah Prihatini Sukma; Ana Khusnul Faizah; Amitasari Damayanti (Prodi Farmasi Fakultas Kedokteran Universitas Hang Tuah, 2022)
Drug interaction is one of the factors that can affect drug activity in the body's response. Drugs can interact with chemicals, herbs, food, and other medications, thereby changing the drug's therapeutic effect. Drug interactions are common in hypertensive and hyperlipidemic patients receiving Calcium Channel Blocker (CCB) and statin therapy. This study uses a narrative review method to examine the effect of drug interactions between statins and calcium channel blockers from articles to analyze rhabdomyolysis. Secondary data is taken from the primary literature, namely journals or articles published in the database (Google Scholar, Pubmed). Drug interactions between statins and CCBs are known to have a severity level due to the administration of amlodipine and simvastatin. This severity can cause rhabdomyolysis and can be identified by pain, muscle weakness, urine color that looks like tea, and measuring CK levels that exceed expected levels (200 U/L). In this study, rhabdomyolysis was shown by increasing creatine kinase (CK) levels by ten times after simvastatin 20 mg and amlodipine 10 mg for one month; other studies also reported that CK levels increased up to 100,000 U/L given atorvastatin 80 mg and amlodipine 5 mg therapy. The effect of drug interactions between statins and CCBs that cause rhabdomyolysis can be detected as early as one month. Treatment of rhabdomyolysis due to drug interactions is replacing statin therapy (simvastatin instead of pravastatin or rosuvastatin).